Kinetic Study and Optimization of the Most Influential Factor on Batch-Extraction of Gingerol from Fresh Ginger (Zingiber officinale) Rhizomes by Using n-Hexane as a Solvent - Margaretha Praba Aulia; Fitra Pradhita; Andri Cahyo Kumoro; Marcelinus Christwardana; H. Hargono (Reaktor, 2018)
A solvent extraction of 6- gingerol from fresh ginger rhizome chips using n-hexane has been successfully carried out. This study aimed to investigate the effects of temperature, feed size, and feed mass on the yield of gingerol, to observe the kinetics of gingerol extraction process using n-hexane as a solvent, to find the most influential parameters in the gingerol extraction process and to determine the optimum conditions of the gingerol extraction process. The experiment was carried out for 60 minutes using two feed mass ( 50 and 75 g), two temperature (60 and 70 oC) and two chips sizes (100 and 25 mm3) using 350 mL n-hexane. The second-order kinetics model was used to study the extraction kinetic parameters. The quick method was used to evaluate the most influential extraction parameters with respect to the yield of gingerol. Feed mass was found to be the most influential parameter in the gingerol extraction process. The optimum extraction conditions were found to be at 60 °C, ginger rhizome chips with 25 mm size3, feed mass was 109.7g and 350 mL n-hexane, which resulted in crude extract with gingerol content of 517.11 ppm.